PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SDN 32/II MUARA BUNGO - Tara Risma Ariani; Abdullah Abdullah; Randi Eka Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was carried out because the learning outcomes of Pancasila Education students in grade V of SDN 32/II Muara Bungo are still low. One of the reasons is the lack of student activity in learning, such as not participating in discussions, not having the courage to express opinions, and not being able to solve the problems given by the teacher. The purpose of this research is to improve student learning outcomes through the application of the Problem Based Learning learning model assisted by puzzle media. The method used is Class Action Research which is carried out in two cycles, each through the stages of planning, implementation, observation, and reflection. The subject of the study is a grade V student of SDN 32/II Muara Bungo. The results showed that the results of teachers' observation sheets increased from 72% to 77% in cycle I, then increased to 83% and 88% in cycle II. The results of students' observation sheets also increased from 68% to 74% in the first cycle, then to 80% and 85% in the second cycle. In addition, the percentage of completeness of student learning outcomes increased from 68% in cycle I to 82% in cycle II so that it has met the indicators of research success. In conclusion, the application of the Problem Based Learning learning model assisted by puzzle media is effective to improve the learning outcomes of Pancasila Education for grade V students of SDN 32/II Muara Bungo.